Multidrug resistance in fungi: regulation of transporter-encoding gene expression - Paul, Sanjoy; Moye-Rowley, W. Scott (Frontiers in Physiology, 2014)
A critical risk to the continued success of antifungal chemotherapy is the acquisition of resistance; a risk exacerbated by the few classes of effective antifungal drugs. Predictably, as the use of these drugs increases in the clinic, more resistant organisms can be isolated from patients. A particularly problematic form of drug resistance that routinely emerges in the major fungal pathogens is known as multidrug resistance. Multidrug resistance refers to the simultaneous acquisition of tolerance to a range of drugs via a limited or even single genetic change. This review will focus on recent progress in understanding pathways of multidrug resistance in fungi including those of most medical relevance. Analyses of multidrug resistance in Saccharomyces cerevisiae have provided the most detailed outline of multidrug resistance in a eukaryotic microorganism. Multidrug resistant isolates of S. cerevisiae typically result from changes in the activity of a pair of related transcription factors that in turn elicit overproduction of several target genes. Chief among these is the ATP-binding cassette-encoding gene PDR5. Interestingly, in the medically important Candida species, very similar pathways are involved in acquisition of multidrug resistance. In both C. albicans and C. glabrata, changes in the activity of transcriptional activator proteins elicits overproduction of a protein closely related to S. cerevisiae Pdr5 called Cdr1. The major filamentous fungal pathogen, Aspergillus fumigatus, was previously thought to acquire resistance to azole compounds (the principal antifungal drug class) via alterations in the azole drug target-encoding gene cyp51A. More recent data indicate that pathways in addition to changes in the cyp51A gene are important determinants in A. fumigatus azole resistance. We will discuss findings that suggest azole resistance in A. fumigatus and Candida species may share more mechanistic similarities than previously thought.